Relação entre a amplitude de dorsiflexão do tornozelo e a cinemática do membro inferior durante a corrida - Santos, Daniel Augusto dos (2016)
The reduction in dorsiflexion has been related to the presence of movement patterns in the knee and hip potentially injurious the patellofemoral joint in various tasks. However, no studies have evaluated the association during running. The aim of this study was to investigate the association between the range of ankle dorsiflexion and the kinematics of the hip, knee and ankle during the stance phase of the running. Were recruited 39 healthy runners of both genders and aged between 18 and 35 years. The evaluation of ankle dorsiflexion amplitude was performed by lunge test. The kinematics of the running on a treadmill was performed using the Qualisys motion capture system. Pearson correlation was performed to evaluate the association between the range of ankle dorsiflexion and kinematic variables. Three kinematic variables were significantly associated with the range of ankle dorsiflexion: peak knee flexion (r = .510, p = .001), peak lateral rotation of the knee (r = -.527, p = .001) and peak ankle dorsiflexion (r= .377, p = .022). Whereas the decreased knee flexion and ankle dorsiflexion, and the increase in lateral rotation of the knee, increase the burden on the patellofemoral joint, limitation of ankle dorsiflexion range may be related to the origin of patellofemoral pain in runners.